European Offshore Technology Conference and Exhibition 1980
DOI: 10.2118/249-1980-ms
|View full text |Cite
|
Sign up to set email alerts
|

Measured Behaviour of Platforms on the Norwegian Continental Shelf

Abstract: Full scale measurements are being conducted on fixed platforms according to the regulations issued by the Norwegian Petroleum Directorate on the collection of environmental and platform performance (E- and P-) data. This paper is mainly concerned with the quasi-static and dynamic behaviour of the platforms. First, a short description of the E-and P-data programme is given followed by some more detailed information on the particular instrumentation install led on typical platforms. Thereafter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…With mandatory requirements for inspection (Det Norske Veritas 1977) and the expense and danger of diver inspection came a flurry of interest in vibrationbased diagnostic systems (Coppolino & Rubin 1980;Kenley & Dodds 1980;Shahrivar & Bouwkamp 1980;Brederode et al 1986). For example, environmental and platform performance (E-and P-) data (Spidsoe et al 1980) were collected, under the responsibility of the platform operator according to the requirements of the Norwegian Petroleum Directorate: 'in order to assess the safety of the load carrying structure of the platforms and their foundation'. The studies resulted in identification of dynamic characteristics and load-response mechanisms for a number of installations on the Norwegian continental shelf.…”
Section: (C ) Offshore Installationsmentioning
confidence: 99%
“…With mandatory requirements for inspection (Det Norske Veritas 1977) and the expense and danger of diver inspection came a flurry of interest in vibrationbased diagnostic systems (Coppolino & Rubin 1980;Kenley & Dodds 1980;Shahrivar & Bouwkamp 1980;Brederode et al 1986). For example, environmental and platform performance (E-and P-) data (Spidsoe et al 1980) were collected, under the responsibility of the platform operator according to the requirements of the Norwegian Petroleum Directorate: 'in order to assess the safety of the load carrying structure of the platforms and their foundation'. The studies resulted in identification of dynamic characteristics and load-response mechanisms for a number of installations on the Norwegian continental shelf.…”
Section: (C ) Offshore Installationsmentioning
confidence: 99%
“…Despite these obstacles, it is of crucial importance to calculate the probability distribution of response as this information is the minimum requirement for efficient probabilistic analysis of offshore structures [8,9]. Previous work has shown that the Pierson-Holmes (P-H) distribution [10] is a reasonably good model for the global response of structures exposed to Morison wave loading when the effect of load intermittency on the response distribution is not severe [3,[11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%